1991
DOI: 10.2307/1381994
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Food-Searching Intensity of Wood Mice (Apodemus sylvaticus) in Fragmented Forests

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 21 publications
2
36
1
Order By: Relevance
“…Others have reported high coastal densities of small mammals, including Peromyscus (McCabe and Cowan 1945;Thomas 1971;Herman 1979), Mus (Berry and Tricker 1969;Efford et al 1988;Rowe-Rowe and Crafford 1992) and shrews (Crocidura, Spencer-Booth 1963;Sorex, Stewart et al 1989), but ours is one of the first to link high coastal or insular densities to the consumption of marine prey. Population densities of small mammals are generally higher on islands than adjacent mainland sites (Gliwicz 1980;Adler and Levins 1994) and a negative relationship between density and area has been reported for both oceanic and freshwater islands as well as isolated habitat 'islands' on land (Smith and Vrieze 1979;Crowell 1983, Tellería et al 1991Nupp and Swihart 1996). These studies and our results contrast with general conclusions of reviews by Conner et al (2000) and Bowers and Matter ( 1997), who reported either a positive or no significant relationship between density and size of habitat patches for most mammals.…”
Section: Effects Of Marine Resources On Rodent Abundancecontrasting
confidence: 99%
“…Others have reported high coastal densities of small mammals, including Peromyscus (McCabe and Cowan 1945;Thomas 1971;Herman 1979), Mus (Berry and Tricker 1969;Efford et al 1988;Rowe-Rowe and Crafford 1992) and shrews (Crocidura, Spencer-Booth 1963;Sorex, Stewart et al 1989), but ours is one of the first to link high coastal or insular densities to the consumption of marine prey. Population densities of small mammals are generally higher on islands than adjacent mainland sites (Gliwicz 1980;Adler and Levins 1994) and a negative relationship between density and area has been reported for both oceanic and freshwater islands as well as isolated habitat 'islands' on land (Smith and Vrieze 1979;Crowell 1983, Tellería et al 1991Nupp and Swihart 1996). These studies and our results contrast with general conclusions of reviews by Conner et al (2000) and Bowers and Matter ( 1997), who reported either a positive or no significant relationship between density and size of habitat patches for most mammals.…”
Section: Effects Of Marine Resources On Rodent Abundancecontrasting
confidence: 99%
“…Bank vole, a typical forest-dwelling rodent, prefers deciduous plant species to conifers (Hjältén et al, 2004) and prefers forests with well-developed lower vegetation (Ecke et al, 2002;Miklós and Žiak, 2002). Wood mouse, on the other hand, is a habitat generalist which also uses open habitats (Hansson, 1978;Tattersall et al, 2001) and thrives in situations where forests meet open land (García et al, 1998;Geuse et al, 1985;Tellería et al, 1991). In fact, in the study by Boyard et al (2008), this rodent species was more abundant in the forest-pasture ecotone than inside forests or pastures in a bocage landscape and was highlighted as the major means of transfer of I. ricinus larvae from woodland to pasture.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, wood mice (Apodemus sylvaticus) which exploit resources within forests and agricultural lands (Montgomery and Gurnell 1985) attain higher numbers at forest edges than within forests or adjacent agricultural lands (Garcia et al 1998). At the landscape scale this translates to higher densities of mice in more highly fragmented landscapes (Geuse et al 1985;Telleria et al 1991). Habitat switching by P. maniculatus between knapweed and adjacent habitats could similarly result in higher mouse population densities at knapweed edges such as herbicide treatment boundaries and agricultural landscapes or at knapweed invasion fronts where high-density knapweed mixes with native habitats in a fine-grained matrix.…”
Section: Discussionmentioning
confidence: 99%